Attributes of Engineers and Engineering Education for the 21st Century World - Sreeram Ramakrishna, P. E.; ., FREng; Khandelwal, Mudrika (Journal of Engineering Education Transformations, 2014)
21st Century is witnessing enrollment of Net generation ( 19 years old)of studentsinto a variety of engineering programs. They have diverse learning aspirations and needs. They wish to learn at their own pace and comfort with peers while leveraging the technology enhanced learning tools. They are open to diverse views, flexible careers, research and innovation careers, and entrepreneurship. They are aware that their workplace will bedifferent from the earlier generations as the businesses leverage supply chains spanning the world and compete to differentiate in the local markets. 21st Century workplaces seek employees with cross-cultures work abilities and global knowledge and experience as they need to interact and move internationally. The Net generation will live longer than earlier generations, and need tobe economically active for longer periods. Learning life-long and regularly upgrading skills and knowledge is the new normal. The Net generation of students have a choice of diverse engineering education providers such as public, private, not-for-profit, for-profit, online, part-time, international branch campuses, and their combinations. They have access to worldwide comparison of engineering schools at the disciplinary level, internationally recognized and accredited engineering programs, and opportunities for the global experience at home and abroad. They are comfortable with digital technology and prefer blended learning methods. Recent decades also saw widening of engineering field covering many new disciplines which flourished at the interfaces with other disciplines. The strong demand for professional qualifications led to the scenario of undergraduate engineering education being akin to liberal arts education with diverse career options. Yet, according to the several mediareports, theemployers are able to find only a fraction of engineering graduates with requisite knowledge, skills, abilities, and attitudes suitable for employment. In other words there is a need to rethink the way the students are inspired and developed, faculty members are prepared, and curriculum and pedagogy are tailored to the needs of the 21st Century workplaces and new generation of students. Systematic engineering education research and thought leadership is needed to produce globally competent engineers. Sharing of best practices and continual improvement in all aspects of engineering education is desired for preparing engineers for the 21st Century. Authors’ affiliated institutions implemented many aspects of engineering education captured in this paper.